American Catholic history : a documentary reader - Massa, Mark Stephen; Osborne, Catherine R., 1979- (New York : New York University, 2008)
"American Catholic History makes available original documents produced in North America from the earliest missionary voyages in the sixteenth century up to the present day. The texts have been selected to illuminate the complex history, beliefs, and practices of what has become North American Roman Catholicism ... offers an overview of the American Catholic experience from both the top down of institutional and intellectual history as well as from the bottom up of social, deveotional, womens and ethnic histories"--Publisher's description.
Frontiers and encounter -- Inside/outside -- Catholicism and the intellectual life -- Politics -- Worship & the spiritual life.
Includes bibliographical references (pages 279-285).
Keywords: Catholic Church -- United States -- History; Catholic Church; United States -- Church history; United States; Katholische Kirche; USA; Church history; History